Assessment of Parameter Estimation Methods for Nonintrusive Loss Estimation of Induction Motors - Becker-Cares, C; Verdejo-Fredes, H (John Wiley and Sons Inc, 2025)
The equivalent circuit method is an accurate and versatile tool to estimate the losses and efficiency of induction motors during energy audits. However, determining the circuit parameters of in-service motors usually involves disrupting their operation. A less intrusive option is to estimate the parameters from performance data provided in catalogues and datasheets. Nine parameter estimation methods are assessed in this work according to accuracy and robustness criteria. Three relatively simple methods stand out with good performance on both criteria. Yet, the combination of high accuracy and total absence of failures is not observed in any of the tested methods. Additionally, a conceptual error repeated in four references regarding the use of the Thévenin equivalent is identified and corrected. Finally, a case study of loss estimation in two tested motors shows that good accuracy is achievable as long as the data reported by the manufacturer matches the real motor characteristics. A mismatch between reported and real characteristics may be detected by comparing the measured input power with its calculated value for the same slip. © 2025 The Author(s). IET Electric Power Applications published by John Wiley & Sons Ltd on behalf of The Institution of Engineering and Technology.
Keywords: equivalent circuits; induction motors; losses; parameter estimation